Performance characteristics of low global warming potential R134a alternative refrigerants in ejector-expansion refrigeration system - Mishra, Shubham; Sarkar, Jahar (Polish Academy of Sciences, 2016)
Performance assessment of ejector-expansion vapor compression refrigeration system with eco-friendly R134a alternative refrigerants (R152a, R1234yf, R600a, R600, R290, R161, R32, and propylene) is presented for air-conditioning application. Ejector has been modeled by considering experimental data based correlations of component efficiencies to take care of all irreversibilities. Ejector area ratio has been optimized based on maximum coefficient of performance (COP) for typical air-conditioner operating temperatures. Selected refrigerants have been compared based on area ratio, pressure lift ratio, entrainment ratio, COP, COP improvement and volumetric cooling capacity. Effects of normal boiling point and critical point on the performances have been studied as well. Using ejector as an expansion device, maximum improvement in COP is noted in R1234yf (10.1%), which reduces the COP deviation with R134a (4.5% less in basic cycle and 2.5% less in ejector cycle). Hence, R1234yf seems to be best alternative for ejector expansion system due to its mild flammability and comparable volumetric capacity and cooling COP. refrigerant R161 is superior to R134a in terms of both COP and volumetric cooling capacity, although may be restricted for low capacity application due to its flammability.
Keywords: Area ratio; COP; Critical temperature; Eco-friendly refrigerant; Optimization; Two-phase ejector